2002
DOI: 10.1063/1.1527229
|View full text |Cite
|
Sign up to set email alerts
|

Size effect on intragranular elastic constants in thin tungsten films

Abstract: The size effect on the elastic constants of nanocrystalline tungsten has been investigated in the case of W/Cu multilayers with two modulation wavelengths (3.1 and 24.0 nm). Tungsten Young's modulus and Poisson's ratio have been measured thanks to a technique coupling x-ray diffraction with in situ tensile testing. It is demonstrated that the in-grain thin film elastic constants are highly microstructure -sensitive: in the "3.1 nm" multilayer, tungsten Poisson's ratio is larger than the bulk one while it is sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 12 publications
4
46
0
Order By: Relevance
“…Elastic constant measurements on tungsten and gold films (thickness around 250 nm) have indeed showed that both softening and stiffening can occur [24,39]. Nanoindentation on thin polystyrene films also yielded a lower surface elastic modulus as compared with the bulk [19].…”
Section: Surface Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…Elastic constant measurements on tungsten and gold films (thickness around 250 nm) have indeed showed that both softening and stiffening can occur [24,39]. Nanoindentation on thin polystyrene films also yielded a lower surface elastic modulus as compared with the bulk [19].…”
Section: Surface Effectsmentioning
confidence: 92%
“…The elastic properties are predicted to be influenced significantly by the presence of grain boundaries in polycrystalline materials, free surfaces in high aspect ratio nanowires and point defects such as vacancies in the oxide nanostructures. For example, experimental results on nanocrystalline tungsten reveal a softening of the elastic constants at the nanoscale [24].…”
Section: Introductionmentioning
confidence: 98%
“…Numerous experimental studies have evidenced a very probable softening of elastic constants in n anostructured materials, in particular the C 44 stiffness coefficient in multilayers with very low (Λ ≤ 3 nm) modulation wavelength [5][6][7]. In previous papers, we described an experimental technique combining in situ tensile testing and x-ray diffraction to extract the Poisson's ratio [8] and the Young's modulus of supported thin metallic films [9] and multilayers [10]. This diffractometric method differs from all the other mechanical, vibration, and acoustic techniques since it allows to measure average in-grain strains, and thus intragranular elastic constants.…”
Section: Measuring Thin Film and Multilayer Elastic Constants By Coupmentioning
confidence: 99%
“…A lot of researches have been performed to investigate the size-dependence of the Young's modulus and other mechanical properties. When measuring Young's modulus variation for material tungsten using the tensile test by considering a W/Cu multilayers, Villain et al [6] found that the Young's modulus measured with the 3 nm-layer thick sample is obviously larger than that of bulk material, while the Young's modulus measured with the 24 nm-layer thick sample is smaller than that of the bulk one. Similarly, for material Gold, Renault et al [7] found that the Young's modulus of a 260 nmthick film is 23% larger than that of the corresponding bulk material by using the tensile test.…”
Section: Introductionmentioning
confidence: 99%